PERAN eSERVICE DALAM MENINGKATKAN KUALITAS PELAYANAN CUSTOMER SERVICE GUNA MENANGANI KELUHAN NASABAH PADA BANK CENTRAL ASIA KCP MARGOMULYO SURABAYA - Is Fadhillah; Ardianta Anastasius (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to investigate the role of eService in improving the quality of customer service to handle customer complaints at Bank Central Asia KCP Margomulyo Surabaya. A qualitative approach was used with a descriptive research type. The data collection techniques used include observation, interviews, and documentation, with the data then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that eService has a significant positive impact in improving the quality of customer service. Features such as independent book printing and replacement, independent account opening, verification using ID cards and fingerprints, 24/7 access, and faster customer service provide a more efficient and convenient experience for customers. Nonetheless, technical constraints on the eService machine, difficulty in use by customers, and possible errors in the machine are challenges that need to be overcome to optimize the utilization of eService. In this context, recommendations are given to continuously improve the technical quality and ease of use of eService in order to provide better service to customers.